Robust deconvolution and control of uncertain and time delay systems - Lin, Jun (2008)
This thesis presents some research results on control and deconvolution estimation for discrete-time linear systems with delay. The thesis focuses on two facets, the first is the robust deconvolution estimation of time-delay systems with stochastic parameter uncertainties and the other is the control of time-delay systems.